GM130-dependent Control of Cdc42 Activity at the Golgi Regulates Centrosome Organization - Kodani, Andrew (The American Society for Cell Biology, 2009)
The physical proximity of the Golgi apparatus and the centrosome is a unique feature of mammalian cells whose functional significance is only poorly understood. Here, we demonstrate that the previously described regulation of centrosome organization and function by the Golgi protein, GM130, involves a Golgi-associated complex consisting of GM130, the Rho GTPase, Cdc42, and its guanine nucleotide exchange factor, Tuba. We identified Tuba as a novel GM130-interacting protein and showed that this association controls Tuba-mediated activation of Cdc42 at the Golgi apparatus. Blocking either Tuba or Cdc42 activity reproduced the GM130 depletion phenotype of aberrant, nonfunctional centrosomes. Expression of constitutively active Cdc42 bypassed the requirement for GM130 in centrosome regulation, indicating that Cdc42 functions downstream of GM130. Our studies demonstrate that Cdc42 has a novel role in controlling centrosome organization in unstimulated cells in addition to its known function as a regulator of centrosome reorientation in stimulated cells. This first description of a regulatory pathway between the Golgi apparatus and the interphase centrosome that complements the known role of Golgi proteins in controlling spindle formation during mitosis and may provide an explanation for the pericentriolar position of the mammalian Golgi apparatus during interphase.